2012
DOI: 10.1124/mol.112.078402
|View full text |Cite
|
Sign up to set email alerts
|

A New 2-Pyrone Derivative, 5-Bromo-3-(3-hydroxyprop-1-ynyl)-2H-pyran-2-one, Suppresses Stemness in Glioma Stem-Like Cells

Abstract: Glioma cells with stem cell properties, termed glioma stem-like cells (GSCs), have been linked to tumor formation, maintenance, and progression and are responsible for the failure of chemotherapy and radiotherapy. Because conventional glioma treatments often fail to eliminate GSCs completely, residual surviving GSCs are able to repopulate the tumor. Compounds that target GSCs might be helpful in overcoming resistance to anticancer treatments in human brain tumors. In this study, we showed that 5-bromo-3-(3-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 40 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Previous studies indicated that a small population of CSCs appear to be responsible for tumor initiation and progression and also for the resistance to conventional treatment (18,19). Recently, isolation, identification and selective eradication of CSCs using targeted drugs have become a major focus in basic and clinical cancer studies (20,21). Therefore, for investigating and developing agents targeting CSCs for cancer therapeutics, a reliable model of CSCs is crucial for basic and preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that a small population of CSCs appear to be responsible for tumor initiation and progression and also for the resistance to conventional treatment (18,19). Recently, isolation, identification and selective eradication of CSCs using targeted drugs have become a major focus in basic and clinical cancer studies (20,21). Therefore, for investigating and developing agents targeting CSCs for cancer therapeutics, a reliable model of CSCs is crucial for basic and preclinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing scientific evidence supports the notion that CSCs are responsible for the cancer's resistance to chemoradiation therapy as well as for its metastatic properties, which lead to poor prognosis for numerous human cancers, including cervical cancer [17][18][19]. To date, methods of identifying CSCs has already become hot points in basic cancer research [20], but no universal markers are currently used for the isolation and identification of CSCs in any particular cancer. This study showed that radiation-resistant cervical cancer cells obtained characteristics of CSCs, showing a high expression of apoptosis inhibitory protein surviving, anti-apoptotic protein Bcl-2, and stem cell markers (Oct4, ABCG2, CD24 and CD44).…”
Section: Discussionmentioning
confidence: 99%